2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037454
|View full text |Cite
|
Sign up to set email alerts
|

Motor imagery EEG classification with optimal subset of wavelet based common spatial pattern and kernel extreme learning machine

Abstract: Performance of motor imagery based brain-computer interfaces (MI BCIs) greatly depends on how to extract the features. Various versions of filter-bank based common spatial pattern have been proposed and used in MI BCIs. Filter-bank based common spatial pattern has more number of features compared with original common spatial pattern. As the number of features increases, the MI BCIs using filter-bank based common spatial pattern can face overfitting problems. In this study, we used eigenvector centrality featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This method has unique advantages in nonstationary signal processing, so it has been widely used in EEG signal processing. Grossman and Morlet proposed the Wavelet Transform (WT) in 1984 [15]. The wavelet transform is a new development of the Fourier transform, and the wavelet transform coefficients can reflect the local information of the signal in the time and frequency domains.…”
Section: Introductionmentioning
confidence: 99%
“…This method has unique advantages in nonstationary signal processing, so it has been widely used in EEG signal processing. Grossman and Morlet proposed the Wavelet Transform (WT) in 1984 [15]. The wavelet transform is a new development of the Fourier transform, and the wavelet transform coefficients can reflect the local information of the signal in the time and frequency domains.…”
Section: Introductionmentioning
confidence: 99%
“…6 depicts that the high neuron activation onset in the FC1 channel appears at approximately 800 msec after stimulation for S8. In other studies, usually the C3 and CZ area are reported as the activated area for imaginary right hand movements [4,31]; whilst in our study, the FC1 and CP6 channels are known as the affected area.…”
Section: Discussionmentioning
confidence: 51%
“…If feature extractions are not performed well, it may result in consistently low performance and non-robust model for EEG motor imagery decoding [17]. Indeed, the performance of a BCI system using motor imagery is greatly depending on how features are extracted [18]. Additionally, the non-stationary nature of EEG and the amount of data generated with fewer electrodes makes it impractical to perform real time classification by manually extracting features [19].…”
Section: Related Workmentioning
confidence: 99%